Conhecimento de futuros professores dos primeiros anos escolares para ensinar probabilidades - Fernandes, José António (2018)
The study presented is aimed to evaluate prospective primary teacher knowledge to teach probability. The study included 62 prospective primary teachers, who were attending the 2nd year of the Bachelor's Degree in Basic Education at a University in Northern Portugal. The students were given two tasks to solve, with two questions each: in the first one, they should determine the probability of an event and in the second, they should find out the correctness or incorrectness of three student resolutions to the first question. Our results emphasize the poor performance of the students and the existence of several semiotic conflicts; the correct determination of probability, in the first question, was most often reflected in the correct classification of the students' resolutions in the second question.